2018
DOI: 10.1021/acsmedchemlett.8b00106
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Selective Estrogen Receptor Degraders (SERDs): Expanding the Toolbox of PROTAC Degrons

Abstract: An effective endocrine therapy for breast cancer is to selectively and effectively degrade the estrogen receptor (ER). Up until now, there have been largely only two molecular scaffolds capable of doing this. In this study, we have developed new classes of scaffolds that possess selective estrogen receptor degrader (SERD) and ER antagonistic properties. These novel SERDs potently inhibit MCF-7 breast cancer cell proliferation and the expression of ER target genes, and their efficacy is comparable to Fulvestran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 33 publications
(64 reference statements)
0
29
0
Order By: Relevance
“…58 Recently, a new PROTAC used nonsteroid selective ER degrader (SERD) was developed to generate more powerful and shorter active molecules to induce the degradation of ER. 66 On the PROTACs against AR, Crews group used enzalutamide to optimally link to a VHL ligand and named the hybrid molecule ARCC-4. 67 They showed that ARCC-4 induced the degradation of AR in not only all prostate cancer cell lines (VCaP, LNCaP, and 22Rv1) but also a breast cancer cell line (T47D).…”
Section: Targeting Nuclear Receptorsmentioning
confidence: 99%
“…58 Recently, a new PROTAC used nonsteroid selective ER degrader (SERD) was developed to generate more powerful and shorter active molecules to induce the degradation of ER. 66 On the PROTACs against AR, Crews group used enzalutamide to optimally link to a VHL ligand and named the hybrid molecule ARCC-4. 67 They showed that ARCC-4 induced the degradation of AR in not only all prostate cancer cell lines (VCaP, LNCaP, and 22Rv1) but also a breast cancer cell line (T47D).…”
Section: Targeting Nuclear Receptorsmentioning
confidence: 99%
“…55 PROTAC molecules contain an ER ligand covalently linked to an E3 ligase, which promotes proteasomal degradation of ER. 55 PROTAC molecules contain an ER ligand covalently linked to an E3 ligase, which promotes proteasomal degradation of ER.…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 99%
“…Proteolysis targeting chimeras (PROTACs) are being developed to degrade the ER and may prove useful in patients who have ER-positive breast cancer. 55 PROTAC molecules contain an ER ligand covalently linked to an E3 ligase, which promotes proteasomal degradation of ER. Preclinical studies showed that the ER PROTAC ARV-471 promoted potent degradation of ER in multiple ER-positive cell line models.…”
Section: Clinical Implications and Therapeutic Strategies To Treat Mbmentioning
confidence: 99%
“…Over the past decade, PROTACs have been developed to address an ever-expanding collection of target proteins. Owing to the availability of well-validated chemical matter to repurpose as PROTAC warheads, the majority of early reports focused on degraders of hormone receptors [10][11][12][13], BET-family proteins [14][15][16] and kinases [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. More recently, the applicability of PROTACs has been broadened to include multi-functional proteins (e.g., TRIM24 [34], SMARCA2 [35] tau [36,37]), and HaloTag7-fused proteins for chemical genetics [38].…”
Section: Introductionmentioning
confidence: 99%